Pengaruh Intervensi Penyuluhan Terhadap Tingkat Pengetahuan Ibu Tentang Penyakit Kecacingan Di Posyandu Baleagung, Grabag, Magelang - Dwii Hastuti; Yulfatussa’diyah (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2022)
Abstract Background: Worms are intestinal parasitic worm infections from the intestinal nematode class that are transmitted through the soil. The prevalence of helminthiasis in the village of Kapoan, Pakis, Magelang found the incidence off egg infection (STH) in vegetables farmers was 0,017% of 60 vegetables farmers. Based on the observations of researches at the research site, there is a lack of knowledege of mothers about the prevention of helminthasis. Objective: to determine the effect of education interventions on the level of mother’s knowledge about the prevention of helminthiasis in Posyandu Baleagung, Grabag, Magelang on February 2022. Method: This researches was conducted using a pre-experimental design method with a one goup pre-test post-test design with a sample of 71 people. Analisis of the data in thi study using SPSS 23. Data analysis was carried out descriptively, then the results obtained were presented in percentages. Results: The results of the researches that were obtained before giving the extension intervention had a good knowledge category of 0%, 59% enough, and 41% less. After giving extension imtervention, there was an increase in the good knowledge category to 87%, 14% emough, and 0% less. Conclusion: there is an effect of education interventions of the knowledge level of the mother on the preventions of worms diseases which can be seen from the results of the Wilcoxon test p (0,000) < 0,05).